IBC-Ox24 Routine Oversewing of Staple Lines to Prevent Leaks is Unnecessary in Patients with Normal Iintraoperative Indocyanine Green (ICG) Perfusion Studies Undergoing Sleeve Gastrectomy. (30th November 2022) - Billy, H; Simpson, T
Abstract:  : Anastomotic staple line leaks following laparoscopic sleeve gastrectomy is a devastating complication. Gastric ischemia and poor tissue perfusion has been hypothesized to be a contributing factor. Various interventions including oversewing of staple lines are commonly used hoping to decrease staple line leaks. Indocyanine green (ICG) can be used to assess bowel perfusion and anastomotic viability following laparoscopic surgery. 50 consecutive patients underwent laparoscopic sleeve gastrectomy utilizing intravenous administration of ICG to assess tissue perfusion and the need for staple line oversewing. Methods: 50 consecutive patients undergoing laparoscopic sleeve gastrectomy were studied intraoperatively after completion of sleeve gastrectomy using intravenous administration of ICG. 7.5 mg of ICG was administered intravenously. Arterial perfusion and end stage tissue perfusion of the completed sleeve gastrectomy was then evaluated. Vascular arterial inflow of the gastric cardia, body and antrum was carefully evaluated both anteriorly and posteriorly for evidence of delayed tissue perfusion or tissue ischemia. Results: In all cases the staple line was examined for staple line formation and evidence of poor tissue perfusion using ICG. Both anterior and posterior evaluation was performed of the distal esophagus, gastric cardia, gastric body and antrum. Absence of tissue perfusion in the resected gastric body was used as a comparison control in all cases. ICG perfusion of the gastric cardia, body and antrum was found to be excellent and brisk in all patients. There were no areas of decreased perfusion or tissue ischemia. Oversewing of the staple line was avoided in all cases. Hemostatic clips were deployed as needed for staple line bleeding until there was no evidence of bleeding on visual inspection and final ICG administration. Patients were followed for evidence of leakage or obstruction for 30 days following completion of the sleeve gastrectomy. There were no leaks, there were no deaths. There were no obstructions and no readmissions. There were no complications related to administration of ICG. Average operative time was 48.7 minutes. Conclusions: Our series of 50 consecutive sleeve gastrectomies utilizing ICG to assess for tissue perfusion demonstrated no evidence of tissue perfusion deficiencies along the staple line or at the angle of His. Staple line oversewing was not used in any patients. Staple line oversewing in cases without evidence of tissue perfusion deficits on ICG evaluation following sleeve gastrectomy is unnecessary. Further multicenter studies and prospective randomized series are necessary to confirm these initial findings.